A different view of curriculum and assessment for severe, complex and profound learning disabilities (New York, NY : Routledge, 2024)
"A Different View of Curriculum and Assessment links a theoretical pedagogical model with a sympathetic practical model of curriculum and assessment difference for those with PMLD, CLD and SLD. Split into two parts, this accessible resource combines theoretical explanations with first-hand accounts of how this works in educational establishments, through the analysis of evidence-based practice carried out in a number of English special (specialist) schools. The expert authors challenge the notion that a national, or common core standards, curriculum, however expertly differentiated, is fit-for-purpose for the PMLD, CLD and SLD populations in any country. A Different View offers cogent and reasoned arguments for considering that irrespective of age, such learners learn differently to their neuro-typical, conventionally developing peers. If they learn differently, this book shows how we should be teaching them differently. Reflecting the centrality of process over product, this book will clearly explain how each individual learner might be enabled and facilitated to become the best they can be and do the best they can do, in order to fully realise their potential as equal and independent citizens"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Learning disabled children -- Education